2017
DOI: 10.4103/sni.sni_90_17
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination against female surgeons is still alive: Where are the full professorships and chairs of departments?

Abstract: Background:Although half of all medical students are now and women are increasingly filling surgical residency positions, few ascend the academic ladder to become chairman of their departments, much less full academic professors.Methods:We queried PubMed to search for the number of women surgeons in different subspecialties, and asked how many were chairman or full academic professors?Results:Data coming out of largely general or cardiothoracic surgery departments cited no substantial gains for women surgeons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“… 25 45 Moreover, despite substantial increases over the past decade in the proportion of US surgical trainees who are women, the proportion of women who are full professors in surgery has remained stagnant. 49 Our findings suggest that male and female surgeons deliver clinical work of equal quality—at least in terms of operative mortality—and reinforce the need to ensure that female surgeons are rewarded equally for their work.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“… 25 45 Moreover, despite substantial increases over the past decade in the proportion of US surgical trainees who are women, the proportion of women who are full professors in surgery has remained stagnant. 49 Our findings suggest that male and female surgeons deliver clinical work of equal quality—at least in terms of operative mortality—and reinforce the need to ensure that female surgeons are rewarded equally for their work.…”
Section: Discussionsupporting
confidence: 55%
“…Previous work has shown that, compared with male surgeons, female surgeons are compensated less and are less likely to be full professors in US medical schools. 24 25 45 46 47 48 49 50 The sex difference in salary tends to be larger among surgical sub-specialties compared with medical specialties. 25 45 Moreover, despite substantial increases over the past decade in the proportion of US surgical trainees who are women, the proportion of women who are full professors in surgery has remained stagnant.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of GD/Bias during Different Stages of Career : A 10-Point Likert Scale was used to code frequency of GD/Bias as None 1 (1), Insignificant (Scores [2] , [3] , [4] ) and Significant (Scores [5] , [6] , [7] , [8] , [9] , [10] ].…”
Section: Methodsmentioning
confidence: 99%
“…In the last few years at least half of the enrolled medical students in the US are female [ 4 ], and while more women are choosing residencies in surgical specialties, there is still a significant absence at the top [ 5 , 6 ]. A 2017 study looking at women as department chairs and full professors showed dismal results, with few women making it beyond the rank of instructor and assistant professor, and even fewer making it to full professor and department chair [ 7 ]. Similar statistics are seen in other developed nations such as Great Britain and Japan, where Kyoto University noted no female associate or full professors in Surgery from 2009 to 2013 [ 8 ], and the Society of British Neurological Surgeons noted that out of 315 neurological surgeons, all 16 full professors were men [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 109 ] High income United Kingdom United States Canada Systematic review No funding 2017 Discrimination against female surgeons is still alive: Where are the full professorships and chairs of departments? [ 110 ] High income United States Systematic review 100% Not reported 2017 E-WIN Project 2016: Evaluating the Current Gender Situation in Neurosurgery Across Europe-An Interactive, Multiple-Level Survey [ 17 ] Lower middle Upper middle and High income 35 countries* Questionnaire n = 12,985 12% Not reported 2017 Gender Differences in the Professional and Personal Lives of Plastic Surgeons [ 111 ] High income United States Questionnaire n = 757 (309/448) 41% Not reported 2016 Gender Differences in Pediatric Orthopedics: What Are the Implications for the Future Workforce? [ 112 ] High income United States Questionnaire n = 62 (18/44) 29% Not reported 2016 The erasure of gender in academic surgery: a qualitative study.…”
Section: Resultsmentioning
confidence: 99%